2020
DOI: 10.1016/j.forsciint.2020.110422
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of strontium isotope ratios in Mexican human hair and tap water as provenance indicators

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…However, because of the complexity of the modern supermarket diet, it is almost impossible to compile the 87 Sr/ 86 Sr ranges of local foods from all traveled locations. As previous studies have shown that the hair samples usually have the same 87 Sr/ 86 Sr as the local tap water (Tipple et al, 2019;Ammer et al, 2020), we chose the 87 Sr/ 86 Sr ratios of the tap water samples in the FAD (Chartrand and St-Jean, 2015) and the river or tap water samples in the literature (Voerkelius et al, 2010;Chesson et al, 2012;Bataille et al, 2020b) to estimate the range of hair 87 Sr/ 86 Sr for the studied individual.…”
Section: Estimate Isotope Ranges From the Forensic Attribution Database And The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the complexity of the modern supermarket diet, it is almost impossible to compile the 87 Sr/ 86 Sr ranges of local foods from all traveled locations. As previous studies have shown that the hair samples usually have the same 87 Sr/ 86 Sr as the local tap water (Tipple et al, 2019;Ammer et al, 2020), we chose the 87 Sr/ 86 Sr ratios of the tap water samples in the FAD (Chartrand and St-Jean, 2015) and the river or tap water samples in the literature (Voerkelius et al, 2010;Chesson et al, 2012;Bataille et al, 2020b) to estimate the range of hair 87 Sr/ 86 Sr for the studied individual.…”
Section: Estimate Isotope Ranges From the Forensic Attribution Database And The Literaturementioning
confidence: 99%
“…Previous studies demonstrated that the 87 Sr/ 86 Sr ratios in hair are strongly related to the 87 Sr/ 86 Sr ratio of local tap water (Tipple et al, 2018(Tipple et al, , 2019Ammer et al, 2020). If the hair of the volunteer recorded the 87 Sr/ 86 Sr ratios of tap water at traveled locations by drinking the tap water and incorporating its 87 Sr/ 86 Sr ratio into hair through the bloodstream like the light stable isotope systems, we would expect large 87 Sr/ 86 Sr variations throughout the predicted profile shown in Figure 5.…”
Section: Comparing the Predicted Isotopic Profile And The Measured Isotopic Values Of Strontiummentioning
confidence: 99%
“…The first reference database for the region was published by Juarez (2008); she measured 87 Sr/ 86 Sr ratios of teeth ( n = 19) collected from current residents of Mexico. More recently, Ammer, Kootker, et al (2020) measured 87 Sr/ 86 Sr ratios of hair ( n = 101) and tap water collected in Mexico and found that they were strongly correlated. This has led investigators to use Sr in combination with C and/or O to predict the likely origin of recovered UBC remains (e.g., Bartelink et al, 2018, 2020; Bartelink & Chesson, 2019; Kramer et al, 2020).…”
Section: Databases and Forensic Applicationsmentioning
confidence: 99%
“…This has led investigators to use Sr in combination with C and/or O to predict the likely origin of recovered UBC remains (e.g., Bartelink et al, 2018, 2020; Bartelink & Chesson, 2019; Kramer et al, 2020). Mapping products (isoscapes) needed for these geolocation efforts are being rapidly created—that is, for Mexico (Ammer, Kootker, et al, 2020; Juarez et al, 2018; see Figure 2), and the circum‐Caribbean region (Bataille et al, 2012; Laffoon et al, 2017; see Figure 3) as well as other parts of the world (Adams et al, 2019; Bataille et al, 2018, 2020; Daux et al, 2021; Gautam et al, 2020; Shin et al, 2020; Wang & Tang, 2020; Zieliński et al, 2021). These products, in conjunction with more regular use of isotope testing, should help foster more widespread application of the technique in the coming years.…”
Section: Databases and Forensic Applicationsmentioning
confidence: 99%
“…For example, environmental mercury pollution can be detected in the hair of humans that have a diet rich in fish [1]. Strontium in our drinking water reflects the distance between the freshwater source and the ocean and can, after becoming preserved in hair, assist forensic investigators in linking unidentified victims to the geographic area in which they lived [2,3]. Additionally, drug use is recorded in hair and can be detected with high temporal precision since hair grows at a known rate [4,5].…”
Section: Introductionmentioning
confidence: 99%